Fim do pragmatismo: as relações entre estado e os ferroviários em Santa Maria/RS durante o primeiro período da ditadura civil-militar no Brasil (1964-1968) - Berni, Antonio Augusto Durgante (2012)
This study aims to examine the relationship between the State and railroad workers of Santa Maria during the first period of the Civil-Military Dictatorship in Brazil between 1964 and 1968. Given this, we seek to establish the main line of work as the idea that in this period due to the violent repression that followed mainly against the most active class-leaders, the pragmatism that characterized the political praxis of the railways during the so-called populist state (1945 -1964) came to an end. Likewise, the role of representative organizations scattered in associations, unions, etc. lost his sense of being due to policy interventions suffered at the summit which led to a depoliticization of workers and take a role especially bureaucratic in relation to conflicts at work. Thus, the railways have been jettisoned not only their influence on the other professional categories in the city, as well as the various spheres of power which had representatives. The issue of torture against political prisoners in Santa Maria was another important issue that has examined and direct connection with the practice intervention and demobilization class carried out by the authoritarian regime that was imposed in the country from 1964.